Landscaping the Status of Nutritional Literacy in Rural India - Shrutiba Zala,; Hemlata Saini,; Kureshi Shahir M, (Journal of Agricultural Extension Management, 2026)
Nutrition has a significant impact on the growth and development of an individual. India is suffering from the double burden of malnutrition i.e., a significant part of its population is affected by both over-nutrition and under-nutrition. One effective measure of fighting malnutrition is to consume balanced, nutritious food loaded with essential nutrients and micro-nutrients. However, to consume healthy diet, the nutrition literacy comprising of nutritional knowledge, attitude and dietary practices to meet nutritional requirement is a pre-requisite. The present study provides a comprehensive understanding of the nutritional literacy landscape of rural India. It also highlights the role of nutritional literacy in driving nutri-sensitive agriculture. The study also throws light on the constraints faced by the rural people in attaining nutritional literacy and policy framework suggestions to overcome them.